Economic, Environmental and International Trade Effects of the EU Directive on Energy Tax Harmonization - Dieter Schumacher; Jochen Diekmann; Katja Schumacher; Michael Kohlhaas; Martin Cames (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
In October 2003, the European Union introduced a Directive which widens the scope of the EU?s minimum taxation system from mineral oils to all energy products including coal, natu-ral gas and electricity. It aims at reducing distortions that currently exist between Member States as well as between energy products. In addition, it increases previous minimum tax rates and thus the incentive to use energy more efficiently. The Directive will lead to changes in the energy tax schemes in a number of countries, in particular some southern Member Countries (Greece, Spain, Portugal) and most of the Eastern European EU candidate countries. In this paper, we analyze the effects of the EU energy tax harmonization with GTAP-E, a computable general equilibrium model. Particular focus is placed on the Eastern European countries which became new members of the EU in May 2004. We investigate the effects of the tax harmonization on overall economic growth and sectoral development. Special atten-tion is paid to international trade in order to analyze if competitiveness concerns which have been forwarded in the context of energy taxation are valid. Furthermore, the effect on energy consumption and emissions and thus the contribution to the EU?s climate change targets is analyzed.
Keywords: C68; Q48; O52; H23; F18; 330